(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
The advancement of communication systems, particularly in antenna design, focuses on achieving low-cost, compact devices with high gain and wide bandwidth. However, at millimeter-wave frequencies, microstrip antennas suffer from severe losses, limiting their performance. Dielectric Resonator Antennas (DRAs), composed of dielectric materials with no metallic losses, offer a promising solution by providing high gain, wide bandwidth, and excellent efficiency for millimeter- wave applications. Despite these advantages, conventional MIMO antennas often use two or three elements with an equal number of ports, resulting in relatively large sizes. To address this limitation, we propose a novel approach utilizing a single- element DRA equipped with three ports for MIMO applications. This design not only reduces the overall antenna size but also optimizes performance. The single-element DRA is initially designed to operate at 26 GHz, with three ports feeding the resonator at distinct orientations.